Use of soybean hulls for the production of conventional panels of low density agglomerates - Guimaraes, Ingrid Luz; Ramos de Araujo Veloso, Maria Cecillia; Nogara Lisboa, Fernando Jesus [UNESP]; Mendes, Rafael Farinassi; Mendes, Lourival Marin; Farrapo, Camila Lais; Guimaraes Junior, Jose Benedito (Univ Federal Rural Pernambuco, 2019)
Wood accounts for more than 40% of the production cost of clad of aglomerates panels and to meet industry demand and reduces the production costs of panels, the use of agro-industrial waste is an alternative. In this sense, the objective of this work was to evaluate the effect of the substitution of wood by soybean hull on the physical and mechanical properties of the panels. The panels were produced with a nominal density of 0.60 g cm(-3). It replaced the percentages of 0, 25, 50, 75 and 100% of soybean hulls in relation to the eucalyptus particles. The particles were glued with 12% of the urea-formaldehyde. The pressing cycle comprised a pressure of 4.0 MPa and a temperature of 180 degrees C for 15 minutes. The results showed that the conventional agglomerated panels produced with soybean residue showed an increase in their physical properties and a reduction of the mechanics as the replacement of the wood by residue was increased. It is concluded that, from the technical point of view, the physical and mechanical properties are met with a maximum substitution of the wood per soybean residue in the proportion of 28.9%.
Keywords: soybean hulls; bonded plates; Eucalyptus; lignocellulosic material